2010
DOI: 10.3928/01484834-20091217-02
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Undergraduate Nursing Research: A Comparison of Traditional and Innovative Approaches for Success with Millennial Learners

Abstract: Historically, nursing students have questioned the value of a nursing research course and have not appreciated the research-practice link. These are important concerns in light of the increasing emphasis on evidence-based nursing practice. The purpose of this study was to develop innovative strategies for teaching undergraduate nursing research that engage millennial learners and emphasize the relationship between evidence-based practice and clinical outcomes. Innovative assignments were developed that include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 11 publications
1
59
0
4
Order By: Relevance
“…In a study by Royse and Newton (2007), the innovative approach of gamification for nursing students is an affirmed technique to enhance students' ability to retain knowledge and motivate them to learn. This finding is supported by McCurry and Martins (2010) who acknowledge that nursing academics should consider innovative approaches to teaching undergraduate nursing students in ways which appeal to millennial learners. For the purpose of this article, millennial leaners belong to the generation born between 1978and 2001(DiLullo et al, 2011.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 52%
“…In a study by Royse and Newton (2007), the innovative approach of gamification for nursing students is an affirmed technique to enhance students' ability to retain knowledge and motivate them to learn. This finding is supported by McCurry and Martins (2010) who acknowledge that nursing academics should consider innovative approaches to teaching undergraduate nursing students in ways which appeal to millennial learners. For the purpose of this article, millennial leaners belong to the generation born between 1978and 2001(DiLullo et al, 2011.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 52%
“…Additionally, teamwork is involved and there is a degree of excitement and entertainment. These components appeal to learners in the Generation Y age bracket (McCurry & Martins, 2010;Dempsey, Haynes, Lucassen, & Casey, 2002;Leach & Sugarman, 2006). Baid and Lambert (2010) further note that there should be adequate planning of the classroom games so that there is -cant differences in outcomes when comparing pre and posttest scores of students who learned via traditional methods versus playing an educational classroom game, i.e., Cowen andTesh (2002), Ingram, Ray, Landeen andKeane (1998).…”
Section: Gamesmentioning
confidence: 99%
“…When surveyed about their usage, 98% of the respondents reported that clickers kept them engaged during the lectures, 84% believed their usage helped them perform betusing them and were in favor of incorporating them in other classes. The clickers would appeal to those in the Generation Y age bracket because -gies (McCurry & Martins, 2010;Partridge & Hallam, 2006). Some hindrances to using clickers in the classroom would be cost, time spent on creating applicable questions, resistance to the technological aspect of the equipment and resistance to change from an educator's typical teaching environment.…”
Section: Clickersmentioning
confidence: 99%
“…infirmières enseignantes ont souvent du mal à élaborer des méthodes pédagogiques engageantes et significatives du point de vue des étudiantes de premier cycle en sciences infirmières (9). Certains auteurs soutiennent que des approches novatrices pour l'enseignement de la recherche en sciences infirmières au premier cycle doivent être mises en place pour favoriser les apprentissages et l'engagement des étudiantes de la génération Y, qui constituent la plus importante proportion des étudiantes actuellement inscrites au niveau du baccalauréat en sciences infirmières au Québec.…”
unclassified